Synthesis of a Hexavalent Betulinic Acid Derivative as a Hemagglutinin-Targeted Influenza Virus Entry Inhibitor - Chen, Yingying; Wang, Xinchen; Zhu, Yinbiao; Si, Longlong; Zhang, Bo; Zhang, Yongmin; Zhang, Lihe; Zhou, Demin; Xiao, Sulong (Molecular pharmaceutics, 2020)
Naturally occurring pentacyclic triterpenes, such as betulinic acid (BA) and its derivatives, exhibit various pharmaceutical activities and have been the subject of great interest, in particular for their antiviral properties. Here, we found a new anti-influenza virus conjugate, hexakis 6-deoxy-6-[4-N-(3β-hydroxy-lup-20(29)-en-28-oate)aminomethyl-1H-1,2,3-triazol-1-yl]-2,3-di-O-acetyl-α-cyclodextrin (CYY1-11, 1), in a mini library of pentacyclic triterpene–cyclodextrin conjugates by performing a cell-based screening assay and then exploring the underlying mechanisms. Our results showed that conjugate 1 possessed a high-level activity against the influenza virus A/WSN/33 with an IC50 value of 5.20 μM (SI > 38.4). The study of the mechanism of action indicated that conjugate 1 inhibited viral replication by directly targeting the influenza hemagglutinin protein (K D = 1.50 μM), thus efficiently preventing the attachment of the virion to its receptors on host cells and subsequent infection. This study suggests that multivalent BA derivatives have possible use as a new class of influenza virus entry inhibitors.